Emerging Research on Bone Health Using High-Resolution CT and MRI - Liebl, Hans; Baum, Thomas; Karampinos, Dimitrios C.; Patsch, Janina; Malecki, Andreas; Schaff, Florian; Eggl, Elena; Rummeny, Ernst J.; Pfeiffer, Franz; Bauer, Jan S. (Current Radiology Reports, 2014)
Today’s most prevalent bone disease in the western hemisphere is osteoporosis. Predominantly postmenopausal women and older men suffer from bone loss caused by an imbalance in the physiological tissue renewal process between bone formation and resorption. As a result, osteoporosis is associated with fragility fractures, disability, impaired bone regeneration and increased mortality. The World Health Organization based the gold standard for diagnosing osteoporosis on bone mineral density (BMD) measurements using dual X-ray absorptiometry. However, BMD measurements are limited in discriminating subjects with and without osteoporotic fractures and have been shown to only partly reflect successful treatment of osteoporotic fractures. Bone microstructure is an integral determinant of bone strength. Today, new high-resolution imaging techniques such as high-resolution peripheral quantitative computed tomography and high-resolution magnetic resonance imaging make it possible to measure three-dimensional bone microarchitecture and volumetric bone mineral density with high accuracy and a relatively low radiation dose.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dark field imaging; High-resolution bone imaging; Magnetic resonance imaging (MRI); Multidetector computed tomography (MDCT); Osteoporosis